2013
DOI: 10.1080/10810730.2012.743620
|View full text |Cite
|
Sign up to set email alerts
|

The Conceptualization and Communication of Risk Among Rural Appalachian Adolescents

Abstract: This study employs a meta-theoretical perspective for examining risk perceptions and behavior in the rural, Appalachian cultural context, an area that remains largely unexplored. In-depth interviews were conducted with 113 rural adolescents to describe how youth conceptualize risk and how risk is communicated in the rural environment. Analyses revealed adolescents viewed behavior as risky when they had personal or vicarious experiences resulting in a loss of control or physical harm. Elements of the rural Appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…Evidence shows that rural youth is more inclined to engage in early onset and frequent use of substances than urban youth and, thus, are at high risk for the targeted behavior (Johnston et al, 2013; Pruitt, 2009). That is, youth substance use is influenced by the physical and social contexts (Miller, Alberts, Hecht, Krizek, & Trost, 2000; Pettigrew, Miller-Day, Krieger, & Hecht, 2011) and environmental factor such as the issue of rurality requires a further investigation (Moreland, Krieger, Hecht, & Miller-Day, 2013). …”
Section: An E–e Perspective On Substance Use Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence shows that rural youth is more inclined to engage in early onset and frequent use of substances than urban youth and, thus, are at high risk for the targeted behavior (Johnston et al, 2013; Pruitt, 2009). That is, youth substance use is influenced by the physical and social contexts (Miller, Alberts, Hecht, Krizek, & Trost, 2000; Pettigrew, Miller-Day, Krieger, & Hecht, 2011) and environmental factor such as the issue of rurality requires a further investigation (Moreland, Krieger, Hecht, & Miller-Day, 2013). …”
Section: An E–e Perspective On Substance Use Preventionmentioning
confidence: 99%
“…For example, rural youth are more likely to cite an “anti-use identity” as an explanation for turning down drug offers as well as avoiding in order to be accountable to parents (Pettigrew et al, 2011). In addition, rural youth are more likely to cite loss of control as a risk based on vicarious experiences (Moreland et al, 2013). As a result, cultural matching of E–E messages to the audience may place a prominent impact on the kiR message outcomes and this lead to the development of a rural version of the curriculum that matches the context of the intended audience.…”
Section: An E–e Perspective On Substance Use Preventionmentioning
confidence: 99%
“…Schools with fewer opportunities for participation in extracurricular sports display increased signs of high‐risk behaviors including arrests, births and the incidence of sexually transmitted infections . A number of studies have indicated that rural adolescents often find their communities lacking in structured recreational opportunities and spend much of their leisure time in the home with friends, where they report accessing and using substances and sharing them among peers…”
Section: Time With Familymentioning
confidence: 99%
“…Effective risk communication requires an understanding of how risks are conceptualised (Moreland, Raup‐Krieger, Hecht, & Miller‐Day, ). Individuals with dementia and family carers may conceptualise risk more as action or consequence than as likelihood (Stevenson & Taylor, ; Stevenson, Savage, & Taylor, in press).…”
Section: Introductionmentioning
confidence: 99%